Pengaruh Motivasi , Lingkungan Kerja , Dan Budaya Organisasi Terhadap Kinerja Karyawan PT Manufaktur Di Cikarang - Muhammad ilham (Jurnal Ekonomi dan Bisnis Digital, 2023)
This study was shown to examine the effect of work motivation on employee performance, the influence of the work environment on employee performance, the influence of organizational culture on employee work. This research uses quantitative methods.